Management of Symptomatic Gallstones in Pregnancy: Gallstone Management in Pregnancy - Hussain, Zahoor; Ali, Zulfiqar; Sirajudin, .; Baker, Abu; Sadaf, .; Hussain, Aijaz (Pakistan Journal of Health Sciences, 2024)
Gallstones, also known as cholelithiasis, are crystalline forms that occur in the gallbladder or biliary tract. Pregnancy causes various physiological changes that raise the chance of gallstone formation, which can lead to difficulties for both the mother and the fetus. Objective: To examine the safety and outcomes of conventional and interventional treatment in pregnant women with symptomatic gallstones. Methods: The study was longitudinal study. This study was conducted in Khairpur Medical College Civil Hospital Khairpur Mirs. The duration of this study was one Year, from Jan 2023 to Dec 2023. A total number of participant was (N=250) in this study. The age of participants was 18-35 years. There were included two treatment conventional and interventional. Results: The mean age of patients was 35.5 years. This study included 250 patients, had experienced gallstone symptoms. The intervention treatment group had the most participants (76%), followed by the conservative treatment group (24%). The cholecystitis participants had conservative treatment (76.3%), followed by laparoscopic treatment (53.3%). The majority participants was (66.6%) got laparoscopic therapy in the second trimester and indicate significant outcomes as compared to third trimester. The pregnant women was experienced no mortality, miscarriage during intervention therapy. Conclusions: This study supported prior findings that laparoscopic cholecystectomy can be performed safely during pregnancy, particularly in the second trimester. However, the third trimester brings additional obstacles, as seen by the higher prevalence of open cholecystectomy.